Do phthalates act as obesogens in humans? A systematic review of the epidemiological literature. (February 2014) - Goodman, Michael; LaKind, Judy S.; Mattison, Donald R.
Abstract Introduction: Phthalates, a class of commonly used compounds with widespread human exposure, have been described as obesogens, or chemicals that disrupt lipid metabolism and produce metabolic changes leading to increased risk of type 2 diabetes mellitus (DM) and cardiovascular disease (CVD). This communication provides a systematic review of the available epidemiologic evidence on associations between phthalate ester metabolites in urine or blood and various health endpoints related to overweight/obesity, DM or CVD. Methods: We followed the current methodological guidelines for systematic reviews to identify, retrieve and summarize the relevant epidemiological literature on the relation between phthalates and overweight/obesity, DM, CVD or related biomarkers. Each eligible paper was summarized with respect to methods and results with particular attention to study design and exposure assessment. As quantitative meta-analysis was not feasible, the study results were assessed qualitatively for inter- and intra-study consistency. Results: We identified 26 publications of epidemiologic studies that assessed associations between either urinary or serum phthalate metabolites and outcomes of interest. These studies represented 18 independent data sources. We found no inter- or intra-study consistency for any phthalate metabolite for any of the indicators of overweight/obesity, DM or CVD in children or adults. Most reported associations were not statistically significantly different from the null, some were positive, and others were inverse. All studies except two used cross-sectional analyses and for this reason could not be used to test causal hypotheses. Conclusion: The current epidemiological data do not support or refute the hypothesis that phthalates act as obesogens in humans.